Inter-fraction robustness of intensity-modulated proton therapy in the post-operative treatment of oropharyngeal and oral cavity squamous cell carcinomas - Hague, Christina (Br J Radiol, 2020)
OBJECTIVE: To evaluate dosimetric consequences of inter-fraction setup variation and anatomical changes in patients receiving multifield optimised (MFO) intensity modulated proton therapy for post-operative oropharyngeal (OPC) and oral cavity (OCC) cancers. METHODS: Six patients receiving MFO for post-operative OPC and OCC were evaluated. Plans were robustly optimised to clinical target volumes (CTVs) using 3 mm setup and 3.5% range uncertainty. Weekly online cone beam CT (CBCT) were performed. Planning CT was deformed to the CBCT to create virtual CTs (vCTs) on which the planned dose was recalculated. vCT plan robustness was evaluated using a setup uncertainty of 1.5 mm and range uncertainty of 3.5%. Target coverage, D(95%), and hotspots, D(0.03cc), were evaluated for each uncertainty along with the vCT-calculated nominal plan. Mean dose to organs at risk (OARs) for the vCT-calculated nominal plan and relative % change in weight from baseline were evaluated. RESULTS: Robustly optimised plans in post-operative OPC and OCC patients are robust against inter-fraction setup variations and range uncertainty. D(0.03cc) in the vCT-calculated nominal plans were clinically acceptable across all plans. Across all patients D95% in the vCT-calculated nominal treatment plan was at least 100% of the prescribed dose. No patients lost ≥10% weight from baseline. Mean dose to the OARs and max dose to the spinal cord remained within tolerance. CONCLUSION: MFO plans in post-operative OPC and OCC patients are robust to inter-fraction uncertainties in setup and range when evaluated over multiple CT scans without compromising OAR mean dose. ADVANCES IN KNOWLEDGE: This is the first paper to evaluate inter-fraction MFO plan robustness in post-operative head and neck treatment.